STRATEGI PEMASARAN DALAM MENINGKATKAN DAYA SAING RESTORAN GOLDEN LEAF KELAPA GADING - Ramon Hurdawaty; Yesi Stephanie Monica (Jurnal Pendidikan dan Perhotelan (JPP), 2024)
The increasing public consumption of food and beverages in recent years has occurred in the world and also in Indonesia. With the increasing interest in purchasing and consumption, the growth of restaurants and restaurant marketing strategies can develop, followed by the ongoing tight competition between each restaurant that has its own characteristics. This study aims to determine the right marketing strategy to increase restaurant competitiveness. This research was conducted at one of the Chinese restaurants located in Kelapa Gading, North Jakarta, namely the Golden Leaf Restaurant. This study uses a qualitative research method with a SWOT analysis through the IFAS, EFAS, IE, and QSPM matrix stages. Data collection techniques used in this study include observation, interviews, documentation, and literature. The results of the SWOT matrix research show that the position of the Golden Leaf Kelapa Gading restaurant is in quadrant I (grow and build) with a total IFAS value of 3.58 (strong) and EFAS of 3.04 (high). There are strengths and opportunities at the Golden Leaf Kelapa Gading restaurant, but this company has weaknesses and threats.